Nilai Relevansi Laba dan Aliran Kas (Studi Empiris pada Perusahaan Manufaktur di Bursa Efek Indonesia Periode 2001-2009) - Joni . (Jurnal Akuntansi)
This study provides information on predictive ability of annual earnings and cash flow from operation numbers. We obtained a sample of 44 BEI listed companies and 352 observation, year-end firms from 2001 to 2009. We find that both cashflows and earnings numbers have substantially predictive ability for future cashflows. Furthermore, this study documents that earnings numbers have more predictive ability for future cashflows than cashflows and the result are robust.